Early single-dose treatment with exosomes provides neuroprotection and improves blood-brain barrier integrity in swine model of traumatic brain injury and hemorrhagic shock. Issue 2 (February 2020) - Williams, Aaron M.; Bhatti, Umar F.; Brown, Jordana F.; Biesterveld, Ben E.; Kathawate, Ranganath G.; Graham, Nathan J.; Chtraklin, Kiril; Siddiqui, Ali Z.; Dekker, Simone E.; Andjelkovic, Anuska; Higgins, Gerald A.; Buller, Benjamin; et al.
Abstract : BACKGROUND: Administration of human mesenchymal stem cell (MSC)–derived exosomes can enhance neurorestoration in models of traumatic brain injury (TBI) and hemorrhagic shock (HS). The impact of early treatment with MSC-derived exosomes on brain injury in a large animal model remains unknown. We sought to evaluate the impact of early single-dose exosome treatment on brain swelling and lesion size, blood-based cerebral biomarkers, and blood-brain barrier (BBB) integrity. METHODS: Female Yorkshire swine were subjected to a severe TBI (12-mm cortical impact) and HS (40% estimated total blood volume). One hour into shock, animals were randomized (n = 5/cohort) to receive either lactated Ringer's (LR; 5 mL) or LR + exosomes (1 × 10 12 exosome particles in 5 mL LR). Animals then underwent additional shock (1 hour) followed by normal saline resuscitation. After 6 hours of observation, brain swelling (% increase compared with the uninjured side) and lesion size (mm 3 ) were assessed. Cerebral hemodynamics and blood-based biomarkers of brain injury were compared. Immunofluorescence and RNA sequencing with differential gene expression and pathway analysis were used to assess the integrity of the perilesion BBB. RESULTS: Exosome-treated animals had significantly less ( p < 0.05) brain swelling and smaller lesion size. They also had significantly decreased ( p < 0.05) intracranial pressures and increased cerebral perfusion pressures. Exosome-treated animals had significantly decreased ( p < 0.05) albumin extravasation and significantly higher ( p < 0.05) laminin, claudin-5, and zonula occludens 1 levels. Differential gene expression and pathway analysis confirmed these findings. Serum glial fibrillary acidic protein levels were also significantly lower ( p < 0.05) in the exosome-treated cohort at the end of the experiment. CONCLUSION: In a large animal model of TBI and HS, early treatment with a single dose of MSC-derived exosomes significantly attenuates brain swelling and lesion size, decreases levels of blood-based cerebral biomarkers, and improves BBB integrity. Abstract : Supplemental digital content is available in the text.